catena-Poly[[diaquabis(2-ethyl-1H-imidazole-κN (3))cadmium]-μ-sulfato-κ(2) O:O′] - Yu, Chua-Hua (International Union of Crystallography, 2012)
In the title one-dimensional coordination polymer, [Cd(SO(4))(C(5)H(8)N(2))(2)(H(2)O)(2)](n), the Cd(II) atom (site symmetry 2) is coordinated by two sulfate O atoms, two water molecules and two 2-ethylimidazole ligands in a distorted cis-CdN(2)O(4) octahedral geometry. The water molecules have a cis disposition. The bridging sulfate ions (site symmetry 2) link the Cd(II) ions into a polymeric chain extending along [001]. The chains are linked by N—H⋯O and O—H⋯O hydrogen bonds. The terminal –CH(3) group of the ligand is disordered over two orientations in a 0.61 (5):0.39 (5) ratio.